PES-Tio2 Mixed Matrix Hollow Fiber Membrane With Anti-Fouling Properties For Humic Acid Removal - Pang, Wen Yu (Universiti Sains Malaysia, 2017)
Recently, studies showed that the irreversible fouling of membrane limited the application of PES membrane in the application of water treatment for removal of humic acid. Large amount of study being performed previously and it been well proven that the fouling of membrane can be mitigated by improving the hydrophilicity of the PES membrane. One of the most studied method to improve PES membrane hydrophilicity is through blending of TiO2 nanoparticle which is a low cost and widely available nanoparticles. However, most of the research regarding PES/TiO2 mixed matrix membrane is being done in flat sheet configuration. Compared to hollow fiber, flat sheet has much limited real application. Looking at this situation, this study has fabricated PES hollow fiber membrane using different TiO2 loading. The blending of TiO2 nanoparticle into the PES membrane is proven to improve the hydrophilicity of the membrane as well as improve the thermal stability of the hollow fiber (HF) membrane due to the well dispersion of TiO2 through the membrane. When the membrane performance is being tested using 50 mg/L of humic acid (HA) solution at pH 7.7, high flux is obtained at lower TiO2 loading but higher HA rejection is obtained at high TiO2 loading. Moreover, at highest TiO2 loading the flux recovery ratio (FRR) can increase up to 99.027 % and the recovery flux ratio (RFR) can reduce to as low as 4.175 %. This indicate that membrane with high TiO2 loading has greater performance. Nevertheless, the intention of this study is to evaluate the anti-fouling properties of the membrane. Based on irreversible resistance and fouling resistance found on the membrane, the resistance on S3 is the lowest showing that it’s most anti-fouling. The S3 membrane has HA permeate flux of 23.851 kg/m2.h under transmembrane pressure of 1 bar with HA rejection up to 97.89 %. S3 is optimum justified based on its acceptable trade-off between permeate flux and HA rejection despite its excellent fouling resistance properties.